Equilibration of athletes' body state in the course of increasing the training intensity - Wei Wang; Elena Kozlova (Universidad de Murcia, 2024)
Recovery of an athlete after injury allows to achieve either the previous results or relatively equal. Moreover, the prescribed drugs or recovery exercises are offered in courses without the possibility of process adjustments. The relevance of the study is determined primarily by a large number of universal methods of restoration, if necessary, development of more patient-specific approach. The novelty of the study is determined by the fact that the human body is a dynamic system, the state of which is different at any time. The authors developed the idea of a stochastic process problem in the form of a system with a variable state, which can be utilized to generate a process, in order to build a technique for recognizing and predicting the state of dynamic systems. The authors showed that the dynamic system of the body can be considered not only as a process element, but also as a structure that allows to fully achieve recovery during the training period of athletes and their off-season indicators. The paper has developed a model that allows to predict the state of the dynamic system and harmonise the load and the recovery process of the athlete's body. The developed method for identifying and predicting the state of dynamical systems with the improvement of the method of covariance functions factorisation makes it possible to determine the main matrices of a dynamical system using the Riccati equation.